Stress effects on working memory, explicit memory, and implicit memory for neutral and emotional stimuli in healthy men - Luethi, Mathias; Meier, Beat; Sandi, Carmen (Frontiers in Behavioral Neuroscience, 2009)
Stress is a strong modulator of memory function. However, memory is not a unitary process and stress seems to exert different effects depending on the memory type under study. Here, we explored the impact of social stress on different aspects of human memory, including tests for explicit memory and working memory (for neutral materials), as well as implicit memory (perceptual priming, contextual priming and classical conditioning for emotional stimuli). A total of 35 young adult male students were randomly assigned to either the stress or the control group, with stress being induced by the Trier Social Stress Test (TSST). Salivary cortisol levels were assessed repeatedly throughout the experiment to validate stress effects. The results support previous evidence indicating complex effects of stress on different types of memory: A pronounced working memory deficit was associated with exposure to stress. No performance differences between groups of stressed and unstressed subjects were observed in verbal explicit memory (but note that learning and recall took place within 1 hour and immediately following stress) or in implicit memory for neutral stimuli. Stress enhanced classical conditioning for negative but not positive stimuli. In addition, stress improved spatial explicit memory. These results reinforce the view that acute stress can be highly disruptive for working memory processing. They provide new evidence for the facilitating effects of stress on implicit memory for negative emotional materials. Our findings are discussed with respect to their potential relevance for psychiatric disorders, such as post traumatic stress disorder.